2018
DOI: 10.1088/1361-6463/aac7e2
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature magnetoelectric effects in multiferroic Y-type hexaferrites

Abstract: Y-type hexaferrites are promising single-phase multiferroics where the electric polarization is induced by conical spin orders. The influence of substitution of Sr and Ni on the magnetic and magnetoelectric properties of Y-type hexaferrite BaSrCo2Fe11AlO22 has been investigated. Sr doping does not change much the Curie temperature TC near 760 K and the saturation magnetization at 300 K. In contrast, the saturation magnetization is reduced by Ni doping. The spin-induced electric polarization can be reversed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The higher magnetic ordering temperature of II relative to the Ba 2 Sn 2 MFe 10– x Ga x O 22 series can be attributed to the isolation of the magnetic layers by the nonmagnetic germanates as well as a lack of nonmagnetic ion mixing onto the magnetic sites. Other hexaferrites exhibiting relatively high temperature ordering include Ba 2 Co 2 Fe 12 O 22 at 613 K, Ba 2 Co 1.5 Ni 0.5 Fe 12 O 22 at 718 K, and BaSrCo 2 Fe 11 AlO 22 at 760 K . The exceptionally high ordering temperature of 855 K in Ba 2 Fe 11 Ge 2 O 22 is in line with that observed in some other Fe rich ferrites.…”
Section: Resultsmentioning
confidence: 66%
“…The higher magnetic ordering temperature of II relative to the Ba 2 Sn 2 MFe 10– x Ga x O 22 series can be attributed to the isolation of the magnetic layers by the nonmagnetic germanates as well as a lack of nonmagnetic ion mixing onto the magnetic sites. Other hexaferrites exhibiting relatively high temperature ordering include Ba 2 Co 2 Fe 12 O 22 at 613 K, Ba 2 Co 1.5 Ni 0.5 Fe 12 O 22 at 718 K, and BaSrCo 2 Fe 11 AlO 22 at 760 K . The exceptionally high ordering temperature of 855 K in Ba 2 Fe 11 Ge 2 O 22 is in line with that observed in some other Fe rich ferrites.…”
Section: Resultsmentioning
confidence: 66%
“…Our hardness and Young's modulus results and previously reported values for c-BN are summarized in Table 1. [20][21][22][23][24][25][26][27] Similar summary for w-BN has been provided in our previous paper. [15] There have been several experimental and calculated reports of the mechanical properties of c-BN sintered compacts but few reports of those properties for c-BN single crystals.…”
Section: Methodsmentioning
confidence: 99%
“…In these multiferroic hexaferrites, a small P is usually induced by the transverse conical spin structure in the hexagonal plane, which can be well interpreted by the spin current model [25] or inverse Dzyaloshinskii-Moriya (DM) interaction [26]. Our recent study showed that the Y-type hexaferrites BaSrCo2Fe11AlO22 and Ba0.9Sr1.1Co2Fe11AlO22 exhibit the ME effect even at room temperature [27]. Therefore, we used these samples to test the magnetic field dependence of αE at room temperature.…”
Section: Materials and Experimentsmentioning
confidence: 99%